Enhanced production of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) with modulated 3-hydroxyvalerate fraction by overexpressing acetolactate synthase in Cupriavidus necator H16 - Jo Young Yun; SOYOUNG PARK; Gong, Gyeongtaek; Roh, Soonjong; Yoo, Jin; Ahn, Jung Ho; Lee, Sun-Mi; Um, Youngsoon; Kim, Kyoung Heon; Ko, Ja Kyong (Elsevier BV, 2023)
The elastomeric properties of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), a biodegradable copolymer, strongly depend on the molar composition of 3-hydroxyvalerate (3HV). This paper reports an improved artificial pathway for enhancing the 3HV component during PHBV biosynthesis from a structurally unrelated carbon source by Cupriavidus necator H16. To increase the intracellular accumulation of propionyl-CoA, a key precursor of the 3HV monomer, we developed a recombinant strain by genetically manipulating the branchedchain amino acid (e.g., valine, isoleucine) pathways. Overexpression of the heterologous feedback-resistant acetolactate synthase (alsS), (R)-citramalate synthase (leuA), homologous 3-ketothiolase (bktB), and the deletion of 2-methylcitrate synthase (prpC) resulted in biosynthesis of 42.5 % (g PHBV/g dry cell weight) PHBV with 64.9 mol% 3HV monomer from fructose as the sole carbon source. This recombinant strain also accumulated the highest PHBV content of 54.5 % dry cell weight (DCW) with 24 mol% 3HV monomer from CO2 ever reported. The lithoautotrophic cell growth and PHBV production by the recombinant C. necator were promoted by oxygen stress. The thermal properties of PHBV showed a decreasing trend of the glass transition and melting temperatures with increasing 3HV fraction. The average molecular weights of PHBV with modulated 3HV fractions were between 20 and 26 x 104 g/mol.